Study of Dimensions of Rādhā’s Vipralambha Śṛṅgāra From Bharatā’s View - B.Shobana; Sujatha Mohan (Formosa Journal of Multidisciplinary Research, 2023)
In Bharatā’s Nāṭya Śāstra, the chapter Sāmānyābhinaya describes ten stages of love and have suggestions for emotionally representing them. Jayadēva’s Gītagovinda, symbolizes the interplay between Rādhā and Kṛṣṇa. The objective of this paper is to identify various dimensions of Rādhā’s love that are analogous to ten stages of love in order to facilitate an artiste to enrich their internal emotions, in turn enriching their overall performance. The findings of this study is that ten stages of love stated by Bharatā are located across 5 Cantos out of 12 Cantos in Gītagovinda. These 5 Cantos express various dimensions of Rādhā’s love that can be related to ten stages of love, however the sequence of the occurrence differs from that listed by Bharatā.